1997
DOI: 10.1515/bchm.1997.378.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Calmodulin by Permeabilized Fibroblasts Overexpressing the Human Epidermal Growth Factor Receptor

Abstract: Detergent-permeabilized EGFR-T17fibroblasts, which overexpress the human epidermal growth factor (EGF) receptor, phosphorylate both poly-L-(glutamic acid, tyrosine) and exogenous calmodulin in an EGF-stimulated manner. Phosphorylation of calmodulin requires the presence of cationic polypeptides, such as poly-L-(lysine) or histones, which exert a biphasic effect toward calmodulin phosphorylation. Optimum cationic polypeptide/calmodulin molar ratios of 0.3 and 7 were determined for poly-L-(lysine) and histones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Figure 1(A) shows the phosphorylation of CaM in the absence and presence of EGF, performed in the first step of the assay in the absence of Ca 2 + (presence of EGTA) as indicated and the phosphorylation of PGT, subsequently assayed in the second step within the same reaction mixture either in the absence of Ca 2 + (EGTA) or in its presence (Ca 2 + ). As we have previously reported, the addition of Ca 2 + just before starting the phosphorylation of PGT in the second step should prevent further phosphorylation of CaM by the EGFR [17,18,33,34]. It can be observed that the phosphorylation of PGT, detected as a smear along the electrophoretic tracks, was higher when P-(Tyr)-CaM became accumulated in the first part of the sequential assay, as compared to control experiments performed in the absence of CaM.…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationmentioning
confidence: 68%
See 4 more Smart Citations
“…Figure 1(A) shows the phosphorylation of CaM in the absence and presence of EGF, performed in the first step of the assay in the absence of Ca 2 + (presence of EGTA) as indicated and the phosphorylation of PGT, subsequently assayed in the second step within the same reaction mixture either in the absence of Ca 2 + (EGTA) or in its presence (Ca 2 + ). As we have previously reported, the addition of Ca 2 + just before starting the phosphorylation of PGT in the second step should prevent further phosphorylation of CaM by the EGFR [17,18,33,34]. It can be observed that the phosphorylation of PGT, detected as a smear along the electrophoretic tracks, was higher when P-(Tyr)-CaM became accumulated in the first part of the sequential assay, as compared to control experiments performed in the absence of CaM.…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationmentioning
confidence: 68%
“…Histone acts as a cationic cofactor for the phosphorylation of CaM and given that, the amount of P-(Tyr)-CaM formed in the assay depends on the CaM-histone ratio used [33,34]. Upon changing this ratio, we observed that the activation of the EGFR in the presence of EGF was directly proportional to the amount of accumulated P-(Tyr)-CaM (result not shown).…”
Section: Egfr-phosphorylated Cam Enhances Egf-dependent Egfr Activationmentioning
confidence: 79%
See 3 more Smart Citations